Occupational asthma due to porcine pancreatic amylase. - Aiken, T C (1997)
A case of occupational asthma in a 41 year old histopathology laboratory technician attributable to a powder preparation of the porcine pancreatic enzyme amylase is reported. The diagnosis was confirmed by a double blind, placebo controlled, inhalation challenge study which showed immediate and late asthmatic reactions associated with a significant increase in airway responsiveness to methacholine.